Treatment of human T-cell acute lymphoblastic leukemia cells with CFTR inhibitor CFTRinh-172. (November 2019) - Liu, Mingfeng; Liao, Huijuan; Chen, Yan; Lin, Ziyuan; Liu, Yanyan; Zhang, Xiaohu; Chan, Hsiao Chang; Sun, Huaqin
Highlights: CFTR inhibitor CFTR-inh172 inhibits human T-ALL cells in vitro. CFTR-inh172 induces alteration of apoptosis and proliferation gene expression. Potential of CFTR-inh172 in human T-ALL treatment. Abstract: Our previous studies have demonstrated that a previously unrecognized role of CFTR in hematopoiesis and acute leukemia. Here, we show that CFTR inhibitor CFTR-inh172 possesses ability to inhibit human T-cell acute lymphoblastic leukemia cells. In detail, CFTR-inh172 inhibited cell proliferation, promoted apoptosis and arrested the cell cycle in human T-cell acute lymphoblastic leukemia cell CCRF-CEM, JURKAT and MOLT-4. Furthermore, transcriptome analysis reveals that CFTR-inh172 induces significant alteration of gene expression related to apoptosis and proliferation. These ﬁndings demonstrate the potential of CFTR inhibitor CFTR-inh172 in human T-cell acute lymphoblastic leukemia treatment.